Pre-Hospital Management of Diarrhoea Among Caregivers with Children Under Five at Princess Marie Louise Children Hospital, Accra - Acheampong, C.A. (University of Ghana, 2013)
The study sought to assess pre-hospital management of diarrhoea and factors affecting it among caregivers with children under five at the PML Children Hospital in the Greater Accra Region. Diarrhoea remains one of the leading causes of morbidity and mortality among children under five at PML Children Hospital despite the undeniable success of interventions such as ORT, appropriate drug therapy, optimal breastfeeding practices over the years. Proper home management can reduce morbidity and mortality due to diarrhoea. The study design was cross- sectional adopting quantitative approach. The study population comprised all caregivers with children under five reporting to PML Hospital with diarrhoea. A total of 120 participants were enrolled into the study. Permission was sought from PML Children Hospital Management where the study was conducted by providing permission letters and ethical clearance. A structured questionnaire was used as a data collection tool for the study. Data collected was analysed using SPSS version16.0. The findings of the study show poor home management of diarrhoea including dietary restrictions during the diarrhoea episode, low use of both RHFs and ORS but high use of other remedies such as antibiotics and anti-diarrhoea to treat diarrhoea. The study also reveals that caregivers’ educational level had no relationship with knowledge about danger signs of diarrhoea, correct use of ORS as well as level of awareness and use of RHFs and ORS. However, a convincing evidence of relationship was established between caregivers’ education and knowledge about causes of diarrhoea as well as health insurance cover and duration of diarrhoea illness before hospital visit. The study recommended a step up in health education programmes on pre-hospital management of diarrhoea nationwide. A major limitation of the study is that it was limited only to PML Children Hospital and therefore the outcome cannot be generalized to the entire country.
Thesis (MSc) - University of Ghana, 2013